Analisis Sistem Pembayaran Upah (Al-Ujrah) Buruh Tani Kelapa Sawit Berdasarkan Persfektif Islam: Studi kasus desa Pulau Tembus Kec. Air Batu Kab. Asahan - Pramana, Alvian Huda; Sirait, Nur Ihsan (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This study aims to determine the wage payment system for oil palm farming workers in Pulau Tuntung village, Kec. Batu Water Kab. Sharpen. Does the payment system for agricultural laborers in this village fulfill the elements as stipulated in the Al-Qur'an and hadith. This research uses a descriptive method with a qualitative approach. Source of data obtained from secondary data and primary data. The data collection technique is by interviewing oil palm plantation owners and farm laborers and conducting direct observations in the village of Pulau Tembus. The results of this study are several farming labor payment systems, there are monthly, weekly and daily depending on the contract between the garden owner and the laborer. The nominal wage of workers is in accordance with the performance of workers. However, the system for paying workers' wages is not in accordance with the Al-Qur'an and Hadith where workers feel they are working because the working hours are not in accordance with the contract and there is no overtime allowance even though they have worked more than the hours stated in the contract.